Preparation of antifog and antibacterial coatings by photopolymerization. (20th February 2014) - Tang, Ruifen; Muhammad, Atif; Yang, Jinliang; Nie, Jun
<x xml:space="preserve">Abstract</x> This paper contains a kind of ultraviolet‐cured antifogging and antibacterial coating. A quaternary ammonium salt (14QAS), which was synthesized in this paper, has been implemented as a monomer. The chemical structure of 14QAS has been confirmed by Fourier transform infrared spectroscopy and nuclear magnetic resonance. The nitrogen atom on the surface of the coatings with 14QAS was observed by X‐ray photoelectron spectroscopy. The Surface wettability of the polymer film was studied by contact angle analysis, which confirmed the hydrophilicity of the coatings with low water contact angle ( 25°). The antifog properties were evaluated under different conditions. The antibacterial activity of coatings with 14QAS reached 99.9% against S. aureus and E. coli. Copyright © 2014 John Wiley & Sons, Ltd.